At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
is there any solutions for that?
i substitute m to the equation, looks like n=9?
while im using synth div. substituting m=2 then working backwards i came up n=9 XD... so confused here :(
sorry my bad.. its -9 XD
okay im dyin here XD. it wont work in the first condition only in the 2nd
-7/2 ? did it work in the 2nd condition? to have 13 as a remainder? because i think i cant have 1 m and 2 different n's.
and that is?
x^3+mx^2+nx-5/x+2 + 2 =x^3+mx^2+nx-5/x and x^3+mx^2+nx-5/x+3+13=x^3+mx^2+nx-5/x Understand ?!
okay just a newbie here and i need solutions or reasons? :)
@nelskie16 :Did you understand : x^3+mx^2+nx-5/x+2 + 2 =x^3+mx^2+nx-5/x and x^3+mx^2+nx-5/x+3+13=x^3+mx^2+nx-5/x ???
@E.ali not even a little...
When the expression x^3+mx^2+nx-5 is divided by x+2 and x+3 the remainders are 2 and 13. Find the values of m and n. Just dig in and start dividing to get 2 equations in m and n to fit .... do you know how to divide polynomials? synthetic division might be easier to run if you can
@amistre64 i can start with that ... hold on
@Hero : OK friend ! But my means was right !:) :D
@amistre64 got 2 equations... on the first one... i got -2n + 4m = 15 2nd one... -3n + 9m = 45 ... then im always stuck with those equations :(
Or just do like this, let \[p(x)=x^3+mx^2+nx-5\] when p(-2)=2 and p(-3)=13 You can find both m and n from this p(-2)=2 \[(-2)^3+m(-2)^2+n(-2)-5=2...(1)\] p(-3)=13 \[(-3)^3+m(-3)^2+n(-3)-5=13...(2)\]
x^3 + mx^2 + nx -5 0 -2 -2m+4 4m-2n-8 -------------------------- -2 | 1 m-2 -2m+n+4 4m-2n-13 = 2 4m -2n = 15 you did good
now its a basic system of equations run -2n + 4m = 15 -3n + 9m = 45 subsitituion or elimination, or however you like to solve them
system??? okay... wait
do the m and n = 15 / 2 ?
-2n + 4m = 15 -3n + 9m = 45 -2n + 4m = 15 -1n + 3m = 15 -2n + 4m = 15 2n - 6m = -30 -------------- -2m = -15; m = 15/2 -2n + 4(15/2) = 15 -2n + 30 = 15 n = 15/2 as well lets give it a try :) dbl chk them to find out
okay .. wait up
didnt work! i think i did it wrong
it works for me ....
how ? i mean the remainder didnt match up when i substitute 15/2 as m and n.
x^3 +15/2 x^2 +15/2x -5 0 -4/2 -22/2 7 -2 1 11/2 -7/2 2 <-- good x^3 +15/2 x^2 +15/2x -5 0 -6/2 -27/2 18 -3 1 9/2 -12/2 13 <-- good
without knowing how you went about your dbl chk, it hard to see where you might have made an error
how did you get -4/2 ? and in the 2nd one why -6/2?
its easier to add and subtract fractions when you have a like denominator
wait got it!!
-2 = -4/2 etc
sorry my bad.. thank you very much. Sorry for stealing some of your time. BTW thanks for helping.
youre welcome, and good luck ;)
the second one is similar in process to the first; but Sams idea might be a good try